STANDARISASI OUTPUT MADRASAH BERBASIS MORAL FOUNDATIONS THEORY: ANALISIS STANDAR KOMPETENSI LULUSAN DAN STANDAR ISI PENDIDIKAN AGAMA ISLAM DI MAS RAUDLATUL FIRDAUS - Ridha Kurniawan; Wahab Wahab (STKIP Pesisir Selatan, 2026)
This study is motivated by the tendency of the education system to place greater emphasis on academic achievement than on the moral development of students, resulting in educational standards being perceived more as administrative tools than as instruments for character development. This study employs a qualitative approach using a case study design at MAS Raudlatul Firdaus. Data collection techniques include interviews, observations, and analysis of curriculum documents, while data analysis utilizes thematic coding based on the five moral foundations—care, fairness, loyalty, authority, and sanctity—with data validation through triangulation of sources and techniques. The results indicate that the Graduate Competency Standards and Content Standards function not only as academic standards but as a system for shaping students’ moral character through the curriculum, instruction, school culture, and assessment systems. However, it was found that the resulting moral structure tends to be dominated by the dimensions of authority and sanctity compared to the dimensions of care and fairness. This finding suggests that educational standards are not neutral but are social constructions that shape students’ moral structures. The theoretical contribution of this study is to expand the examination of educational standards as a system of moral standardization from the perspectives of moral theory and the sociology of education.